Efeitos da ingestão de cafeína sobre a contribuição anaeróbia e o desempenho em ciclismo de 4.000m após depleção de glicogênio muscular - Cavalcante, Marcos David da Silva (2012)
Several research has shown that caffeine ingestion (1, 2, 7 trimethylxanthine) increases performance. Due to these findings and their removal from the list of banned substances in 2004 by the international anti doping agency, athletes of various sports have widely used caffeine in order to increase performance during competitions. Studies have shown an increase in performance in high-intensity exercise after caffeine ingestion. The increase in performance with the use of caffeine in this type of performance, seems to be related to increasing the anaerobic contribution . On the other hand, depletion of glycogen stores appear to reduce performance during high intensity exercise. This reduction according studies appears to be due to a reduction of the anaerobic contribution. More recently, research has been conducted in order to investigate whether supplementation of carbohydrate with the addition of caffeine provides the additional effect on performance. Thus, the goal of this dissertation was: 1) review the main findings about the effects on performance in time trial and what the mechanisms involved in the combined supplementation of caffeine and carbohydrate (review article). 2) verify if intake of caffeine can reverse the impairment in performance and anaerobic contribution caused by depletion of muscle glycogen during 4000m cycling time trial (results article). In the studies reviewed in the review article found that most studies with combined ingestion of caffeine and carbohydrate showed a further increase in performance. However, more studies need to be performed to elucidate what are the mechanisms of action during time trial arising from the combined ingestion of caffeine and carbohydrate. In the article results the caffeine reversed the performance impaired prior by depletion of muscle glycogen and anaerobic contribution increased to levels above the conditions with muscle glycogen depletion with ingestion of placebo and control